Respuesta :
Answer: 2(−x+y=−2)
2(−x+y=−2)
1(2x−3y=4)
Becomes:
−2x+2y=−4
2x−3y=4
Add these equations to eliminate x:
−y=0
Then solve−y=0for y:
−y=0
−y/-1 = 0/-1 (Divide both sides by -1)
y=0
Step-by-step explanation:
Now that we've found y let's plug it back in to solve for x.
Write down an original equation:
−x+y=−2
Substitute 0 for y in −x+y=−2:
−x+0=−2
−x=−2(Simplify both sides of the equation)
−x/-1 = -2/-2 (Divide both sides by -1)
x=2
Answer:
x=2 and y=0
Answer: x=y+2
Step-by-step explanation:
Step 1: Add -y to both sides.
−x+y+−y=−2+−y
−x=−y−2
Step 2: Divide both sides by -1.
-x/-1 = -y - 2/-1
asnwer: x=y+2
Answer: x = 3/2y + 2
2x−3y=4
Step 1: Add 3y to both sides.
2x−3y+3y=4+3y
2x=3y+4
Step 2: Divide both sides by 2.
2x/2 = 3y + 4/2
answer: x = 3/2y + 2